PENGARUH SIKAP KEWIRAUSAHAAN DAN MODAL USAHA TERHADAP PENDAPATAN UMKM MAKANAN OLAHAN DI KABUPATEN JEPARA - Achmad Rondi; Rekno Djohar Juliani; Dewi Fatmasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to test and analyze the influence of entrepreneurial attitudes and business capital on the income of processed food MSMEs in Jepara district. The population in this research are all entrepreneurs who are members of the MSME Center for processed food products in Jepara Regency with a total of 70 people. The sample used is a saturated sample, so everything is the population. The research results show that the entrepreneurial attitude variable partially has a positive and significant effect on MSME income. The business capital variable partially has a positive and significant effect on MSME income. The variables of entrepreneurial attitude and business capital simultaneously influence MSME income. Having capital, business experience, assisted by an entrepreneurial attitude can increase business income.